Pengaruh Budaya Organisasi Terhadap Kesuksesan Manajemen Proyek Teknologi Informasi: Studi Kasus Perguruan Tinggi di Indonesia - Setiawan, Chanief Budi; Himawan, Arif; Wati, Krisna Mutiara (Jurusan Sistem Informasi Fakultas Ilmu Komputer Universitas Sriwijaya, 2025)
Initiatives to develop IT projects in the education sector have shown significant potential to improve the quality of learning in Indonesia. Effective IT project management is crucial to the progress of this IT project. Nevertheless, the study reveals that from 2017 to 2021, there were obstacles in the form of a relatively high number of project failures (61%), and only 18% of information technology initiatives were successful. This study is designed to assist organizations in identifying and managing critical factors in their organizational culture to achieve success in IT project management as part of their efforts to achieve national technological resilience. The respondents in this study were lecturers and education personnel at universities in Indonesia who met specific criteria, including their involvement in information technology initiatives at their institutions. This investigation employed a convenience sampling method in conjunction with a non-probability sampling technique. According to the analysis, the success of information technology project management was significantly enhanced by organizational culture, which encompassed communication, awards and incentives, learning, and cooperation. The study's findings can assist Indonesian firms in recognizing and controlling key elements of their organizational culture that contribute to the success of IT project management inside their establishments, hence enhancing Indonesia's technological resilience as a whole.